STUDI VEGETASI HUTAN RAWA AIR TAWAR DI CAGAR ALAM RIMBO PANTI, SUMATERA BARAT - Yusuf, Razali; Purwaningsih, Purwaningsih (BERITA BIOLOGI, 2009)
A Vegetation study of some different freshwater swamp forests in Rimbo Panti Nature Reserve, West Sumatera was carried out with a quadrat methode.The results of a floristic inventory of trees with DBH e" 10 cm show that 136 species of 90 genera in 402 families ,presented by 1676 individuals, with the total basal area of 53.11 m occurred in the 5 hectare sample plots.The two leading families in terms of number of species were Euphorbiaceae and Lauraceae while according to the the total sum of importance values for families were Euphorbiaceae, Moraceae and Bignoniaceae.We recorded 19 species of Euphorbiaceae, constituting14.4% of the total species with the basal area of 39.4 % of the total in the three plots. Terminalia copelandii(Combretaceae) was the most prominent species occurring here and was one of the ten leading species. The species-area curves rose steadily up to an area of 1.0 hectare, with a very slight indication of levelling off at about 2 hectares, indicating high Heterogenity particulary in the permanently flooded swamp forest. Four largest trees were Artocarpus rotundatus (DBH = 100.50 cm) Chydenanthus excelsus (DBH = 92.50 cm), Haplophragma macrolobum (DBH = 83.00) and Anthocephalus chinensis (DBH= 75.10 cm).